Kinetics of Spontaneous Bimetallization between Silver and Noble Metal Nanoparticles. Issue 15 (25th June 2018) - Hirakawa, Kazutaka; Kaneko, Tetsuya; Toshima, Naoki
Abstract: A physical mixture of polymer‐protected Ag nanoparticles and Rh, Pd, or Pt nanoparticles spontaneously forms Ag‐core bimetallic nanoparticles. The formed nanoparticles were smaller than the parent Ag nanoparticles. In the initial process of this reaction, the surface plasmon absorption of Ag nanoparticles diminished and then almost ceased within one hour. Within several minutes, the decrease in Ag surface plasmon absorption could be analyzed by second‐order reaction. This reaction was accelerated with an increase of temperature and the energy gap in the Fermi level between Ag and the other metals. The activation energy ( E a ) of this reaction could be determined. An electron transfer reaction from Ag to other metal nanoparticles was proposed as the initial interaction between these metal nanoparticles because the Fermi level of Ag is relatively high, and the electron transfer is possible in terms of energy. The Marcus plot between the rate constant and the driving force, roughly estimated from the work function of metals, and the observed E a values reasonably explained the proposed electron transfer mechanism. Abstract : Protected species : A physical mixture of polymer‐protected Ag nanoparticles and Rh, Pd, or Pt nanoparticles spontaneously forms Ag‐core bimetallic nanoparticles. An electron transfer reaction from Ag to other metal nanoparticles is proposed as the initial interaction between these metal nanoparticles.